A RhNiP/rGO hybrid for efficient catalytic hydrogen generation from an alkaline solution of hydrazine. Issue 38 (19th September 2016) - Du, Xiaoqiong; Tan, Shiyi; Cai, Ping; Luo, Wei; Cheng, Gongzhen
Abstract : A transition metal phosphide based hybrid RhNiP/rGO has been synthesized through a simple one-pot co-reduction method, and further used as a highly efficient catalyst for catalytic dehydrogenation of hydrazine for the first time. This excellent catalytic performance is suggested to be attributed to the synergistic electronic effect between P and Rh–Ni nanoalloys after P doping. Abstract : Transition metal phosphide based hybrids (RhNiP/rGO) with different phosphorus contents have been successfully synthesized via a facile one-pot co-reduction route. Thanks to the synergistic electronic effect between Rh, Ni, and P, the as-synthesized RhNiP/rGO hybrid exhibits superior catalytic activity toward hydrogen generation from an alkaline solution of hydrazine.